2014
DOI: 10.5114/aoms.2013.39938
|View full text |Cite
|
Sign up to set email alerts
|

ST-segment changes in high-resolution body surface potential maps measured during exercise to assess myocardial ischemia: a pilot study

Abstract: IntroductionThe aim of the study was to assess myocardial ischemia by analysis of ST-segment changes in high-resolution body surface potential maps (HR-BSPM) measured at rest and during an exercise stress test.Material and methodsThe study was carried out on a group of 28 patients with stable coronary artery disease and 15 healthy volunteers. The HR-BSPM were measured at rest and during the exercise stress test on a supine ergometer. The workload was increased in stages by 25 W every 2 min, beginning at 50 W. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…This suggests that HR-BSPM may reveal hidden information important in reliable IHD diagnostics. This is in accordance with our preliminary findings in which ischemic changes in the ECG signal were observed in non-standard electrode locations, often in the absence of changes in standard ECG leads 13,1517,34…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…This suggests that HR-BSPM may reveal hidden information important in reliable IHD diagnostics. This is in accordance with our preliminary findings in which ischemic changes in the ECG signal were observed in non-standard electrode locations, often in the absence of changes in standard ECG leads 13,1517,34…”
Section: Introductionsupporting
confidence: 93%
“…This is in accordance with our preliminary findings in which ischemic changes in the ECG signal were observed in non-standard electrode locations, often in the absence of changes in standard ECG leads. 13 , 15 17 , 34 …”
Section: Introductionmentioning
confidence: 99%
“…3 of Ref. 17 [1517]. It is suggested that the ventricular repolarization wave moved toward the back, in the duration from ST to T. It was possibly due to the anatomical facts that the ventricular apex was slanted toward the front and the base toward the back, and that the APD of the apex was shorter than that of the base.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the maps of T-wave alternans coefficient values showed strong differentiation in the level of the received TWA signals on the location of the receiving electrode on the thorax. In some of the examined patients the T-wave alternans would not have been detected using the traditional standard twelve-lead system, as a diagnostically important signal level was recorded in the leads outside the standard layout [ 20 22 ].…”
Section: Discussionmentioning
confidence: 99%